Risk factors for development of transient tachypnea of newborn (Latakia University Journal -Medical Sciences Series, 2022)
Background: Transient tachypnea of the newborn (TTN) is one of the most important acute respiratory diseases in the newborn period caused by delay in absorption of fetal lung liquid.Objectives: The aim of this study was to describe risk factors for  development of transient  tachypnea of newborn.Methods: This is a case -control study of 70 infants were diagnosed with TTN during a period from the 1st of august  2020 to the 1st of august  2021 in the neonatal intensive care unit at Tishreen University Hospital in Lattakia . 70 healthy babies born in the same period were selected as a group control.SPSS software was used for data analysis, P value